(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In this study, morphological and immunohistochemical changes in the lymphoid structures of the thymus of white outbred rats with alimentary iron deficiency were studied. Histological analyses revealed a violation of parenchymal-stromal balance in the organ, a decrease in morphometric indicators of lymphoid tissue, the number of lymphoid cells, and the level of expression of immunohistochemical markers. In immunohistochemical studies, a significant decrease in the expression of markers CD3, Ki-67, and Bcl-2 was noted, which indicates a negative effect of iron deficiency on the proliferation, differentiation, and immunocompetence of T-lymphocytes. The research results have scientific and practical significance in the in-depth analysis of iron deficiency-associated immunodeficiency states and the development of strategies for their correction.